Ternal And External Drivers Towards Intention And Actual Green Building Adoption In Saudi Arabia - Alkahtani, Asem (2024)
The green building rating systems (gbrs) are considered to be the best means of assessing the sustainability and environmental performance of building projects. However, there is limited evidence that focuses on investigating internal and external drivers that may influence the intention to adopt and actual adoption of gbrs. Therefore, this study fills the existing gap by conducting an empirical study that examines the internal and external drivers that influence the intention to adopt and actual adoption of gbrs. This study integrated the technology, organizational, and environmental framework (toe) and institutional theory to examine the internal drivers, including knowledge and information, cost and risk, and human resources, as well as external drivers such as market demand and government support influencing construction companies' top management intention to adopt gbrs, which in turn result in the actual adoption of gbrs. These theories were relevant as they provided structured approaches to analyze the adoption and development of sustainable technologies and practices in the context of green buildings. The study employed convenience sampling techniques with simple random sampling to select the respondents. A survey was conducted by using the online google form method to collect 521 valid and reliable responses. Structural equation modeling using smart pls version 3 software was employed to test and confirm the study’s hypotheses. The findings show that cost and risk,